2009
DOI: 10.1007/s11430-009-5008-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic features of gas-condensate reservoirs in the Kekeya Field, southwest depression in the Tarim Basin, China

Abstract: Oils, condensates and natural gases in the Kekeya Field, southeast depression of the Tarim Basin were studied for their geochemical characteristics. According to the distribution analysis of the C 2 /C 3 values with C 1 /C 2 values, C 2 /C 3 values with C 1 /C 3 values, as well as C 2 /C 3 values with dryness index, there are two different types of natural gases in the studied field, which are spatially regularly distributed. One is the oil cracking gas, located on shallow reservoirs over X 5 2 reservoir, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This may be caused by the high thermal maturity of their sources (Figure 10e), which facilitates the generation of these compounds resistant to thermal stress. On the other hand, multiple extensive gas charging and cap gas leakage from the reservoirs are also considered to play a part role as indicated by the loss of n-C10-n-C14 (Figure 12) [45], which agrees with previous studies [21,46]. For Group III/IV oils, this is assumed to be induced by the mixing of oils originated from the same source at different thermal maturity levels.…”
Section: Thermal Maturity Of Crude Oils and Hydrocarbon Mixingsupporting
confidence: 88%
See 1 more Smart Citation
“…This may be caused by the high thermal maturity of their sources (Figure 10e), which facilitates the generation of these compounds resistant to thermal stress. On the other hand, multiple extensive gas charging and cap gas leakage from the reservoirs are also considered to play a part role as indicated by the loss of n-C10-n-C14 (Figure 12) [45], which agrees with previous studies [21,46]. For Group III/IV oils, this is assumed to be induced by the mixing of oils originated from the same source at different thermal maturity levels.…”
Section: Thermal Maturity Of Crude Oils and Hydrocarbon Mixingsupporting
confidence: 88%
“…It is only constrained around the location of Well KS101, since no vital geochemical diagnostic can be detected to indicate the relevant input of Jurassic-associated oils in the other wells. This may be attributed to the vertically permeable passageways around Well KS101, which is indicated by the strong gas washing and leakage (Figure 12) [21,46]. Moreover, its greater burial depth after subsidence from 65-20 Ma results in enough oil can be generated from Jurassic source rocks and then migrate upward to the Cretaceous reservoirs [4,19,48].…”
Section: Possible Oil Sourcesmentioning
confidence: 99%
“…Tetraethyl orthosilicate (Abbreviation TEOS, technical grade) was obtained from Chengdu Kelong Co., Ltd. FC3721, also known as Zonyl FSK, technical grade, structure given as [9]: [3][4][5][6][7][8] was purchased from Shanghai Futian Chemical Technology. Concentrated ammonia and anhydrous ethanol (analytical grade) were obtained from Chengdu Kelong Co., Ltd. Condensate oil, natural gas and natural cores were obtained from the Yaha condensate gas field.…”
Section: Experimental Materials and Instruments Experimental Materialsmentioning
confidence: 99%
“…Research showed that the wetting property near the borehole played a key role in the process of condensate gas recovery [2,3]. In 2000, Li proposed that one of the best ways to increase the production capacity of gas wells was to change the wetting ability from strong liquid wettability to gas wettability in the condensate gas reservoirs [4,5].…”
Section: Introductionmentioning
confidence: 99%